Penerapan Zachman Framework pada Perancangan Architecture Sistem Informasi Pengelolaan Obat Dinas Kesehatan Purbalingga - Annisa Dwi Risqi; Achmad Fauzan; Tito Pinandita; Feri Wibowo (Fakultas Teknik Universitas Muhammadiyah Bengkulu, 2025)
The application of the right information system architecture framework is very important in ensuring efficiency and consistency in data management, especially in drug management information systems in the government sector. This study aims to evaluate the maturity level of the application of the Zachman Framework in the design of the Drug Management Information System at the Purbalingga Health Office using the Capability Maturity Model (CMM) approach. The evaluation was conducted on six main perspectives of Zachman: Planner, Owner, Designer, Builder, Subcontractor, and Functioning System. The measurement results showed the following maturity percentage values: Planner (60%), Owner (40%), Designer (60%), Builder (40%), Subcontractor (20%), and Functioning System (60%), with an average maturity level of 46.67% or equivalent to Level 2 (Repeatable). These results indicate that the design process already has a basic pattern but has not been thoroughly documented or standardized. The main recommendation in this research is to improve technical documentation, HR training, and integration between architecture perspectives to achieve a higher level of maturity.